Volumetric differences suggest involvement of cerebellum and brainstem in chronic migraine. (April 2016) - Bilgiç, Başar; Kocaman, Gülşen; Arslan, Ali Bilgin; Noyan, Handan; Sherifov, Resul; Alkan, Alpay; Asil, Talip; Parman, Yeşim; Baykan, Betül
Background: Chronic migraine (CM) is a disabling neurologic condition that often evolves from episodic migraine. There has been mounting evidence on the volumetric changes detected by magnetic resonance imaging (MRI) technique in migraineurs. These studies mainly focused on episodic migraine patients and less is known about the differences in CM patients. Method: A total of 24 CM patients and 24 healthy control individuals (all females) were included in this study. All participants underwent neurological examination and MRI. High-resolution anatomical MRI images were processed with an automated segmentation method (FreeSurfer). White-matter abnormalities of the brain were also evaluated with the Age-Related White-Matter-Changes Scale. Results: The volumes of the cerebellum and brainstem were found to be smaller in CM patients compared to healthy controls. White-matter abnormalities were also found in CM patients, speciﬁcally in the bilateral parieto-occipital areas. There was no correlation between the clinical variables and volume decrease in these regions. Conclusion: CM patients showed significant volume differences in infratentorial areas and white-matter abnormalities in the posterior part of the brain. It is currently unclear whether the structural brain changes seen in migraine patients are the cause or the result of headaches. Longitudinal volumetric neuroimaging studies with larger groups, especially on the chronification of migraine, are needed to shed light on this topic.